Alumina porous ceramic with hierarchical porous structure and preparation method thereof
By introducing nanowire structures and directional pores into porous alumina ceramics, a porous structure with high porosity is formed, the problem of single pore structure of alumina porous ceramics is solved, and its fluid filtration and hydrophobic properties are improved, thus achieving efficient fluid Filtration and oil adsorption effect.
Patent Information
- Application Number
- CN202411401226.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-09
- Publication Date
- 2025-01-07
AI Technical Summary
The pore structure of existing alumina porous ceramics is relatively single, which is difficult to meet the demand for fluid filtration performance, and the pore size distribution of corundum alumina (α-Al2O3) is poor.
The preparation method of nanowire composite alumina porous ceramics is adopted. By introducing porous hierarchical structures and nanowire secondary structures of directional pores, combined with freeze-drying method and sintering technology, a porous structure with high porosity is formed to improve fluid filtration performance.
The high porosity and excellent mechanical properties of alumina porous ceramics are achieved, and the performance of them as catalyst-loaded materials and fluid filter materials is improved, especially through the introduction of nanowire structures, which improves hydrophobic properties and oil adsorption rates.
Smart Images

Figure CN119263877A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of porous ceramics, and in particular relates to an alumina porous ceramic with a graded porous structure and a preparation method thereof. Background Art
[0002] Porous materials have the characteristics of high porosity, low density, large specific surface area and selective permeability. Among them, porous ceramic materials are widely used because of their good mechanical properties, excellent oxidation resistance and corrosion resistance, and low thermal expansion at high temperatures. Corundum-phase alumina (α-Al2O3) is a common porous ceramic material with the advantages of excellent high-temperature stability, high chemical inertness and good mechanical strength. It can be used as thermal insulation materials, refractory materials and proppants. However, as an isotropic porous ceramic material, corundum-phase alumina (α-Al2O3) has a relatively simple pore structure and relatively poor adjustability of pore size distribution, which makes it difficult to fully meet the performance requirements of fluid filtration. Summary of the invention
[0003] In view of the deficiencies in the prior art, an object of the present invention is to provide an alumina porous ceramic.
[0004] Another object of the present invention is to provide a nanowire composite alumina porous ceramic, which uses corundum phase alumina (α-Al2O3) with good physical and chemical stability as a matrix, introduces a porous hierarchical structure of directional channels and other secondary structures, and has a higher porosity and oil adsorption rate.
[0005] Another object of the present invention is to provide a method for preparing alumina porous ceramics, which comprises converting boehmite powder into corundum phase alumina (α-Al2O3) with a chip interlocking structure, using it as a matrix, and distributing ice as a pore-forming agent in the alumina matrix in a direction thereof. The solvent is removed by freeze-drying to form a hierarchical porous structure and obtain a higher porosity.
[0006] Another object of the present invention is to provide a method for preparing nanowire composite alumina porous ceramics. This method introduces other secondary structures, such as nanowires, through the directional macropores constructed inside the alumina porous ceramic matrix, thereby ensuring that the alumina porous ceramics obtain a higher porosity while improving its performance as a fluid filtration material.
[0007] The purpose of the present invention is achieved through the following technical solutions.
[0008] A method for preparing porous alumina ceramics comprises the following steps:
[0009] Step 1, mixing boehmite powder, a sintering aid, a catalyst, a dispersant, a pH adjuster and a solvent, and ball milling to obtain a ceramic slurry, wherein the ratio of boehmite powder, sintering aid, catalyst, dispersant, pH adjuster and solvent is (50-55): (1-5): (5-20): (0.1-1): (0-10): (55-65) by mass;
[0010] In step 1, the sintering aid is silicon dioxide, the catalyst is aluminum fluoride trihydrate (AlF3·3H2O), the dispersant is a mixture of isobutylene maleic anhydride copolymer (Isobam-104) and triammonium citrate (TAC), the pH regulator is tetramethylammonium hydroxide (TMAH), and the solvent is deionized water.
[0011] In the step 1, the content of the isobutylene maleic anhydride copolymer (Isobam-104) in the dispersant is 90-91 wt%.
[0012] In the step 1, the rotation speed of the ball mill is 200 to 210 r / min, and the ball milling time is 13 to 17 hours.
[0013] Step 2, placing the ceramic slurry in a mold and letting it stand for 10 to 24 hours, freezing it for 6 to 12 hours, vacuum drying it, and demolding it to obtain a green body;
[0014] In step 2, the mold is a cavity with an open top surface, the bottom surface of the mold is made of copper, and the side wall of the mold is made of polyvinyl chloride (PVC).
[0015] In the step 2, the standing temperature is room temperature.
[0016] In step 2, the freezing temperature is -70 to -40°C.
[0017] In step 2, the vacuum drying temperature is -10 to 20° C., and the vacuum drying time is 48 to 72 hours.
[0018] Step 3, sintering the green body at 1000-1500° C. for 1-3 hours to obtain porous alumina ceramics.
[0019] In the step 3, the green body is sintered at 1000-1500° C. for 1-3 hours in an air atmosphere or a nitrogen atmosphere.
[0020] In the step 3, the temperature is increased to 1000-1500° C. at a heating rate of 1-3° C. / min.
[0021] A method for preparing nanowire composite alumina porous ceramics comprises the following steps:
[0022] The alumina porous ceramic is placed in an impregnation solution for vacuum impregnation for 5 to 10 minutes, kept at 24 to 250° C. for 12 to 72 hours to solidify the impregnation solution, and sintered at 1000 to 1500° C. for 1 to 3 hours to obtain a nanowire composite alumina porous ceramic.
[0023] In the above technical solution, the impregnation solution is a silicone resin or a glucose-silica sol mixture.
[0024] In the above technical solution, the glucose-silica sol mixed solution includes: a glucose aqueous solution and a silica sol. Calculated by the amount of substances, the ratio of carbon element in the glucose aqueous solution to silicon element in the silica sol is (0.9-1.1):(3-9).
[0025] In the above technical solution, the glucose aqueous solution includes: glucose monohydrate and water, and the ratio of glucose monohydrate to water in the glucose aqueous solution is (9.9-29.7):(38-42) by mass.
[0026] In the above technical scheme, the method for preparing the silica sol includes: uniformly mixing tetraethyl orthosilicate (TEOS), water and anhydrous ethanol, adding hydrochloric acid to make the pH value 3-4, and magnetically stirring for 8-12 hours to obtain silica sol. In terms of mass fractions, the ratio of tetraethyl orthosilicate (TEOS), water and anhydrous ethanol in the method for preparing the silica sol is (19-21): (6-8): (54-56).
[0027] In the above technical solution, sintering is carried out at 1000-1500° C. for 1-3 hours in an air atmosphere or a nitrogen atmosphere.
[0028] In the above technical solution, the temperature is increased to 1000-1500° C. at a heating rate of 1-3° C. / min.
[0029] Compared with the prior art, the present invention has the following beneficial effects:
[0030] (1) The alumina porous ceramics and nanowire composite alumina porous ceramics of the present invention have a porosity of 78-85% and a compressive strength of less than or equal to 0.6 MPa. They both have good high temperature resistance, excellent mechanical properties and high porosity.
[0031] (2) The alumina porous ceramics and nanowire composite alumina porous ceramics of the present invention can be used as catalyst loading materials and fluid filtration materials. The alumina porous ceramics have less water adsorption after hydrophobic treatment. After the introduction of nanowire structure and hydrophobic treatment, the nanowire composite alumina porous ceramics have better hydrophobic properties, and the oil adsorption rate reaches 77.75%.
[0032] (3) The preparation method of the present invention adjusts the freezing direction to obtain alumina porous ceramics with a graded porous structure having directional channels, which is convenient for introducing various other secondary structures. The preparation method is simple and easy to operate. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] Figure 1 The microstructure scanning electron microscope morphology images of the alumina porous ceramics prepared in Examples 1 and 3 and the nanowire composite alumina porous ceramics prepared in Examples 4 to 5;
[0034] Figure 2 X-ray diffraction patterns of the alumina porous ceramics prepared in Examples 1 to 2 and the nanowire composite alumina porous ceramics prepared in Example 5;
[0035] Figure 3 is the compression deformation curve of the alumina porous ceramic prepared in Example 2;
[0036] Figure 4 The pore size distribution curve of the alumina porous ceramic prepared in Example 2;
[0037] Figure 5 (a) is an electron microscope image of silicon carbide nanowires in the nanowire composite alumina porous ceramics prepared in Example 5, and (b) is a SAED image of silicon carbide nanowires in the nanowire composite alumina porous ceramics prepared in Example 5;
[0038] Figure 6 (a) is a photograph of the nanowire composite alumina porous ceramic prepared in Example 5 after water was added to the surface after hydrophobic treatment, (b) is a photograph of the oil-water mixture, (c) is a photograph of the oil-water adsorption experiment at 0 h, (d) is a photograph of the oil-water adsorption experiment at 8 h, (e) is a photograph of the oil-water mixture after 8 h of the oil-water adsorption experiment, and (f) is a photograph of the nanowire composite alumina porous ceramic prepared in Example 5 after soaking in the oil-water mixture for 8 h. DETAILED DESCRIPTION
[0039] The technical solution of the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments.
[0040] Boehmite powder was purchased from Shandong Zibo Yingchuan Aluminum Co., Ltd.;
[0041] Aluminum fluoride trihydrate (AlF3·3H2O), silica, tetramethylammonium hydroxide (TMAH), hexamethyldisilazane, and n-hexane were purchased from Aladdin;
[0042] Hydrochloric acid was purchased from Tianjin Fengchuan Chemical Reagent Technology Co., Ltd., with a concentration of 36-38 wt%;
[0043] Isobutylene maleic anhydride copolymer (Isobam-104) was purchased from Kuraray Elastomer Division;
[0044] Triammonium citrate (TAC) was purchased from Beijing Bailingwei Technology Co., Ltd.;
[0045] Tetraethyl orthosilicate (TEOS) and anhydrous ethanol were purchased from Komiou;
[0046] Silicone resin (model: SP3100) was purchased from Hao Silicon Technology Co., Ltd.;
[0047] The model of XRD testing instrument is: ARL Equinox 3000, France;
[0048] The model of the SEM testing instrument is: FEI Verios 460L, Germany.
[0049] In the following embodiments, the mold is assembled from a short PVC water pipe and a copper sheet, and the copper sheet is fixed to the opening on the bottom surface of the short PVC water pipe. The size of the mold is Φ27mm×3.5cm, where Φ represents the diameter.
[0050] In the following embodiments, the glucose-silica sol mixed solution includes: a glucose aqueous solution and a silica sol. Calculated by molar fraction, the ratio of carbon element in the glucose aqueous solution to silicon element in the silica sol is 1:6.
[0051] In the following embodiments, the glucose solution comprises: glucose monohydrate and water, and the ratio of glucose monohydrate to water in the glucose solution is 19.8:40 by mass.
[0052] In the following embodiment, the method for preparing silica sol includes: uniformly mixing tetraethyl orthosilicate (TEOS), water and anhydrous ethanol, adding hydrochloric acid to make pH = 4, and magnetically stirring for 8 hours to obtain silica sol. In terms of mass fractions, the ratio of tetraethyl orthosilicate (TEOS) to water and anhydrous ethanol in the method for preparing silica sol is 20.824:7.2:55.284.
[0053] In the following examples, the compressive strength was tested using an electronic universal testing machine.
[0054] Example 1
[0055] A method for preparing porous alumina ceramics comprises the following steps:
[0056] Step 1, mixing boehmite powder, a sintering aid, a catalyst, a dispersant, a pH regulator and a solvent, and ball milling at 200 r / min for 15 hours to obtain a ceramic slurry, wherein the sintering aid is silicon dioxide, the catalyst is aluminum fluoride trihydrate (AlF3·3H2O), the dispersant is a mixture of isobutylene maleic anhydride copolymer (Isobam-104) and triammonium citrate (TAC), the pH regulator is tetramethylammonium hydroxide (TMAH), and the solvent is deionized water. The content of isobutylene maleic anhydride copolymer (Isobam-104) in the dispersant is 91wt%, and the ratio of boehmite powder, sintering aid, catalyst, dispersant, pH regulator and solvent is 51:3:6:0.33:4.32:60 by mass;
[0057] Step 2, placing the ceramic slurry in a mold, standing at room temperature of 20-25° C. for 18 hours to stabilize the network, covering the mold with pearl cotton after standing, freezing at -70° C. for 10 hours by freeze drying, and then vacuum drying at -10° C. for 72 hours, demolding, and obtaining a green body;
[0058] Step 3, placing the green body in a high temperature furnace, heating the temperature to 1300° C. at a heating rate of 2° C. / min in an air atmosphere, and sintering at 1300° C. for 2 hours to obtain alumina porous ceramics.
[0059] The porosity of the alumina porous ceramic prepared in Example 1 is 81.94%, the compressive strength is 0.347 MPa, and the density is 0.61 g / cm 3 , the specific surface area is 6.718m 2 / g.
[0060] Example 2
[0061] A method for preparing porous alumina ceramics is basically the same as that of Example 1, except for step 3. Step 3 of Example 2 is to place the green body in a high-temperature furnace, heat the temperature to 1200°C at a heating rate of 2°C / min in an air atmosphere, and sinter at 1200°C for 2h to obtain porous alumina ceramics.
[0062] The porosity of the alumina porous ceramic prepared in Example 2 is 83.72%, the compressive strength is 0.356 MPa, and the density is 0.60 g / cm 3 , the specific surface area is 6.563m 2 / g.
[0063] Example 3
[0064] A method for preparing alumina porous ceramics is basically the same as that of Example 1, except that in step 1, in step 1 of Example 3, the ratio of boehmite powder, sintering aid, catalyst, dispersant, pH regulator and solvent is 51:3:6:0.33:8.64:60 by mass.
[0065] Example 4
[0066] A method for preparing nanowire composite alumina porous ceramics, comprising the following steps: placing the alumina porous ceramics prepared in Example 1 in an impregnation solution (the impregnation solution is a silicone resin) for vacuum impregnation for 10 minutes, placing it in a muffle furnace after impregnation, heating it to 250°C at a heating rate of 2°C / min in an air atmosphere and keeping it at 250°C for 2 hours to solidify the silicone resin, then heating it to 1450°C at a heating rate of 2°C / min in a tubular furnace in a nitrogen atmosphere and sintering it at 1450°C for 2 hours to obtain nanowire composite alumina porous ceramics.
[0067] Example 5
[0068] A method for preparing nanowire composite alumina porous ceramics, comprising the following steps: placing the alumina porous ceramics prepared in Example 1 in an impregnation solution (the impregnation solution is a glucose-silica sol mixture) for vacuum impregnation for 10 minutes, after impregnation, first placing the alumina porous ceramics in a 40°C oven for 72 hours to solidify the glucose-silica sol mixture, and then heating the temperature in a tubular furnace at a heating rate of 3°C / min to 1400°C under a nitrogen atmosphere and sintering at 1400°C for 3 hours to obtain the nanowire composite alumina porous ceramics.
[0069] The porosity of the nanowire composite alumina porous ceramic prepared in Example 5 is 83.72%, the compressive strength is 0.568 MPa, and the density is 0.63 g / cm 3 , the specific surface area is 8.599m 2 / g.
[0070] Figure 1 The microstructure scanning electron microscope morphology of the alumina porous ceramics prepared in Examples 1 and 3 and the nanowire composite alumina porous ceramics prepared in Examples 4 to 5 is shown in FIG. Figure 1It can be seen that the alumina porous ceramics prepared in Example 1 and Example 3 have a pore structure inside, and the internal pore structure is the pores formed by the interlocking of alumina wafers and the pores formed by ice sublimation, and the pores grow perpendicular to the mold base. This is because the copper on the bottom of the mold has better thermal conductivity than the PVC on the side wall of the mold, which makes the ice grow faster in the vertical direction; the nanowire composite alumina porous ceramics prepared in Example 4 and Example 5 not only have pores formed by the interlocking of alumina wafers and the pores formed by ice sublimation, but also silicon carbide nanowires are present in the pores formed by ice sublimation.
[0071] Figure 2 The X-ray diffraction patterns of the porous alumina ceramics prepared in Examples 1 to 2 and the nanowire composite porous alumina ceramics prepared in Example 5 are shown in FIG. Figure 2 It can be seen that the main crystalline phase of the alumina porous ceramics prepared in Examples 1 to 2 is corundum phase alumina (α-Al2O3), and the main crystalline phase of the nanowire composite alumina porous ceramics prepared in Example 5 is corundum phase alumina (α-Al2O3), and the X-ray diffraction peak of silicon carbide (3C-SiC) nanowires can be observed.
[0072] Figure 3 is the compression deformation curve of the alumina porous ceramic prepared in Example 2. Figure 3 It can be seen that the compression deformation curve has a peak at 0.356 MPa. After the peak, the alumina porous ceramics prepared in Example 2 are not damaged and can continue to withstand pressure under the action of external pressure.
[0073] Figure 4 is the pore size distribution curve of the alumina porous ceramic prepared in Example 2, Figure 4 It can be seen that the curve with pore diameter greater than 1000nm is the pore size distribution curve formed after ice sublimation, and its most probable pore diameter is 30158nm. The curve with pore diameter between 0 and 1000nm is the pore size distribution curve formed by the interlocking of alumina wafers, and its most probable pore diameter is 227nm.
[0074] Figure 5 (a) is an electron microscope image of the silicon carbide nanowires in the nanowire composite alumina porous ceramics prepared in Example 5. Figure 5 From (a), we can see that the diameter of silicon carbide nanowires is 160-210 nm; Figure 5 (b) is the SAED image of the silicon carbide nanowires in the nanowire composite alumina porous ceramics prepared in Example 5. Figure 5 As can be seen from (b), by comparing the PDF standard card of silicon carbide (3C-SiC) nanowires, it is determined that the crystal phase of the nanowire composite alumina porous ceramic prepared in Example 5 is 3C-SiC.
[0075] Oil-water adsorption experiment:
[0076] Hydrophobic agent: Hexamethyldisilazane and n-hexane are mixed to obtain a hydrophobic agent, wherein the ratio of hexamethyldisilazane to n-hexane is 3:7 by mass.
[0077] Oil-water mixture: Mix 5g of vacuum pump oil with 20g of water to obtain an oil-water mixture.
[0078] The ceramic is immersed in a hydrophobic agent for 24 hours for hydrophobic treatment, taken out and dried in an oven at 40°C for 24 hours, and the weight is recorded as m1. The dried ceramic is immersed in an oil-water mixture for 8 hours, taken out and weighed after immersion, and recorded as m2. The immersed ceramic is dried in an oven at 40°C for 24 hours, and the weight is recorded as m3. The ceramic is one of the alumina porous ceramic prepared in Example 1 and the nanowire composite alumina porous ceramic prepared in Example 5.
[0079]
[0080] After hydrophobic treatment, the alumina porous ceramics prepared in Example 1 had a mass m1 of 5.6285 g. After soaking in an oil-water mixture, the mass m2 of the alumina porous ceramics prepared in Example 1 was 8.8922 g. After further drying, the mass m3 of the alumina porous ceramics prepared in Example 1 was 8.5822 g, a decrease of 0.31 g, which is also the amount of water adsorbed on the surface of the alumina porous ceramics prepared in Example 1. The water adsorption rate was 5.51%. After calculation, the oil adsorption of the alumina porous ceramics prepared in Example 1 for the oil-water mixture was 2.9537 g, and the oil adsorption rate was 52.48%.
[0081] After the hydrophobic treatment, the mass m1 of the nanowire composite alumina porous ceramic prepared in Example 5 is 4.3950 g. After being soaked in the oil-water mixture, the mass m2 of the nanowire composite alumina porous ceramic prepared in Example 5 is 7.8521 g. After further drying, the mass m3 of the nanowire composite alumina porous ceramic prepared in Example 5 is 7.8121 g, which is a decrease of 0.04 g. This value is also the water adsorption amount of the alumina porous ceramic surface prepared in Example 5, and the water adsorption rate is 0.91%. The oil adsorption amount of the alumina porous ceramic prepared in Example 5 for the oil-water mixture is 3. 4171g, and its oil adsorption rate is 77.75%. The above results show that after soaking in the oil-water mixture and drying, the mass of the alumina porous ceramics prepared in Example 1 is much less than that of the nanowire composite alumina porous ceramics prepared in Example 5, that is, more water is adsorbed. This is because the silicon carbide (3C-SiC) nanowire structure in the nanowire composite alumina porous ceramics prepared in Example 5 has relatively better hydrophobic properties after hydrophobic treatment, which more effectively reduces the adsorption of water by the nanowire composite alumina porous ceramics prepared in Example 5. Therefore, the introduction of nanowires improves the hydrophobic properties of the sample.
[0082] Figure 6 (a) is a photograph of the surface of the nanowire composite alumina porous ceramic prepared in Example 5 after water was added after the hydrophobic treatment. Figure 6 (b) is a photo of an oil-water mixture. Figure 6 (c) is a photo of the oil-water adsorption experiment at 0h. Figure 6 (d) is a photo of the oil-water adsorption experiment at 8h. Figure 6 (e) is a photo of the oil-water mixture after 8 hours of oil-water adsorption experiment. Figure 6 (f) is a photograph of the nanowire composite alumina porous ceramic prepared in Example 5 after being immersed in the oil-water mixture for 8 hours. Figure 6 (a) shows that after the hydrophobic treatment, the surface of the nanowire composite alumina porous ceramic prepared in Example 5 is hydrophobic to water. Figure 6 (f) shows that the nanowire composite alumina porous ceramic prepared in Example 5 adsorbs vacuum pump oil. Figure 6 (b) and Figure 6 (e) further illustrates that the nanowire composite alumina porous ceramic prepared in Example 5 absorbs a large amount of vacuum pump oil and less water.
[0083] The present invention is described above by way of example. It should be noted that, without departing from the core of the present invention, any simple deformation, modification or other equivalent replacement that can be made by those skilled in the art without inventive effort falls within the protection scope of the present invention.
Claims
1. A method for preparing porous alumina ceramics, characterized in that: The following steps are involved: Step 1, mixing boehmite powder, a sintering aid, a catalyst, a dispersant, a pH adjuster and a solvent, and ball milling to obtain a ceramic slurry, wherein the ratio of boehmite powder, sintering aid, catalyst, dispersant, pH adjuster and solvent is (50-55): (1-5): (5-20): (0.1-1): (0-10): (55-65) by mass; Step 2, placing the ceramic slurry in a mold and letting it stand for 10 to 24 hours, freezing it for 6 to 12 hours, vacuum drying it, and demolding it to obtain a green body; Step 3, sintering the green body at 1000-1500° C. for 1-3 hours to obtain porous alumina ceramics.
2. The preparation method according to claim 1, characterized in that: The sintering aid is silicon dioxide, the catalyst is aluminum fluoride trihydrate, the dispersant is a mixture of isobutylene maleic anhydride copolymer and triammonium citrate, the pH regulator is tetramethylammonium hydroxide, the solvent is deionized water, and the content of isobutylene maleic anhydride copolymer in the dispersant is 90-91wt%.
3. The preparation method according to claim 1, characterized in that: The rotation speed of the ball mill is 200-210 r / min, and the ball milling time is 13-17 h.
4. The preparation method according to claim 1, characterized in that: The mold is a cavity with an open top surface, the bottom surface of the mold is made of copper, and the side wall of the mold is made of polyvinyl chloride.
5. The preparation method according to claim 1, characterized in that: In step 2, the standing temperature is room temperature; In step 2, the freezing temperature is -70 to -40°C; In step 2, the vacuum drying temperature is -10 to 20°C, and the vacuum drying time is 48 to 72 hours; In the step 3, the green body is sintered at 1000-1500° C. for 1-3 hours in an air atmosphere or a nitrogen atmosphere; In the step 3, the temperature is increased to 1000-1500° C. at a heating rate of 1-3° C. / min.
6. A method for preparing nanowire composite alumina porous ceramics, characterized in that: The method comprises the following steps: placing the alumina porous ceramics according to claim 1 in an impregnation solution for vacuum impregnation for 5 to 10 minutes, keeping the temperature at 24 to 250° C. for 12 to 72 hours to solidify the impregnation solution, and sintering at 1000 to 1500° C. for 1 to 3 hours to obtain nanowire composite alumina porous ceramics.
7. The method according to claim 6, characterized in that The impregnation solution is an organic silicon resin or a glucose-silica sol mixture, and the glucose-silica sol mixture includes: a glucose aqueous solution and a silica sol. Calculated by the amount of substances, the ratio of carbon element in the glucose aqueous solution to silicon element in the silica sol is (0.9-1.1): (3-9).
8. The method according to claim 7, characterized in that The glucose aqueous solution comprises: glucose monohydrate and water. Calculated by mass, the ratio of glucose monohydrate to water in the glucose aqueous solution is (9.9-29.7):(38-42).
9. The method according to claim 7, characterized in that: The method for preparing the silica sol comprises: uniformly mixing tetraethyl orthosilicate, water and anhydrous ethanol, adding hydrochloric acid to adjust the pH to 3-4, and magnetically stirring for 8-12 hours to obtain the silica sol. In terms of mass fractions, the ratio of tetraethyl orthosilicate, water and anhydrous ethanol in the method for preparing the silica sol is (19-21): (6-8): (54-56).
10. The method according to claim 6, characterized in that The temperature is raised to 1000-1500° C. at a heating rate of 1-3° C. / min, and sintered at 1000-1500° C. for 1-3 hours in an air atmosphere or a nitrogen atmosphere.
Citation Information
Patent Citations
Method for preparing mullite porous ceramic by gel refrigeration drying process
CN101037345A
A method for preparing dual-pore porous ceramics
CN102285815A
Method for preparing aluminum oxide porous ceramic with composite structure by adopting freeze drying process
CN102432327A
SiC nano-wire reinforced porous ceramic composite material and preparation method thereof
CN109020628A
Method for preparing YSZ fiber-based porous ceramic by water-based gel casting
CN109437946A